Aplikasi E-Voting Dalam Pemilihan Ketua Osis Untuk Masyarakat Tingkat SMA dan SMK - Randi Rian Putra; Fahmi Kurniawan; Dwi Saraswati; Sri Handayani (STMIK Budi Darma, 2023)
The election of the OSIS Chair at the high school and vocational school level plays an important role in forming student leadership. However, conventional methods of selection are often inefficient and prone to unclear results. This research develops an e-voting application to facilitate the election of OSIS Chairpersons in SMA and SMK in Growth Village. This application was designed with the aim of increasing integrity, transparency and efficiency in the election process. Based on trials carried out, this e-voting application shows a significant increase in the accuracy of results and voter satisfaction compared to traditional methods. Apart from that, this application is also easily accessible to the people of Growth Village, thereby increasing voter participation.